Current practice of physical therapists in outpatient stroke rehabilitation: a cross-sectional survey in Baden-Württemberg and Thuringia / Arbeitsweise von Physiotherapeut*innen in der ambulanten Schlaganfallrehabilitation: eine Querschnittsumfrage in Baden-Württemberg und Thüringen - Diermayr Gudrun; Schomberg Maria; Barthelmes Lisa-Sophia; Greisberger Andrea; Elsner Bernhard; Salbach Nancy Margaret (Sciendo, 2021)
Guidelines recommend task-oriented training and the use of standardized assessments to improve stroke-related mobility deficits. However, the German outpatient physical therapy prescription catalogue does not include these recommendations resulting in a possible gap between guideline recommendations and clinical practice. Therefore, the purpose of this study was to describe physical therapy practice patterns of stroke-related mobility deficits in the outpatient setting exemplified by the states Baden-Württemberg and Thuringia.